The Dramaturg Director in the Kurdish Theatrical Show The play (The Nights Sing Her Songs) is a model (Journal of the College of Basic Education, 2023)
Summary of the research :The research aims at the relationship between the director and the dramaturg, and the changes that occurred in the different stages, as the dramaturg has become one of the contributors to the structure of the modernist theatrical performance and beyond, because of the aesthetic and intellectual characteristics of his work. The research seeks to reveal the formulas and levels of the dramatic function in theatrical presentation . The research consists of four chapters. The first chapter deals with a problem that is limited to the following question: What does the dramaturg director do in the Kurdish theatrical show? The aims of the research were:1- What are the levels of dramatic work in theatrical performance?2- What are the dramatic formulas in theatrical performance?And the spatial limit: Kirkuk year (2021). As for the objective limit, it was determined: what are the levels of dramaturgy in the Kurdish theatrical show, and the terms were defined procedurally: dramaturge, discourse, dramaturge text. In the second chapter, two topics emerged1- The first signs of dramaturgy.2- Dramaturgy and scripts for theatrical performances.A theatrical sample was chosen: (The Nights Sing Its Songs), and it was analyzed in the light of the descriptive analytical method, and the tool was: what resulted from the theoretical framework, reading the text, following up the exercises, watching the show and observing in its light, and the results were discussed in the fourth chapter, and the conclusions were drawn, the most important of which are: 1- It appeared that the text of the show had multiple levels of drama, the dramaturgy of the script of the director, the actor and the technician. 2- Manipulating the construction of characters and scenes contributed to a radical change in the main idea of the text of the show. Recommendations were identified, and the research was appended to sources, references, and the appendix.Research extracted from a PhD thesisKeywords: dramaturge, dramaturge director, dramaturge text.